The Quality of Comb and Packaged Honey in the Bojongmurni Beekeeping Area,Bogor District, West Java Indonesia (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2026)
Comb honey is honey that remains in the hive and has not undergone extraction, while packaged honeyis commercial honey available in the market. This study aimed to analyze the quality of comb honeyand packaged honey from the Bojongmurni Beekeeping Area, Bogor District, West Java Indonesia.Each type of honey was analysed directly without any pretreatment, with with 20 replicates for eachphysical test and three replicates for each chemical test. Physical tests (solubility, turbidity foam,hexagonal pattern, and heating tests) were analyzed descriptively based on effectiveness values (%),whereas chemical tests (moisture content, water insoluble solids, hydroxymethylfurfural (HMF), anddiastase enzyme activity) were analyzed descriptively using mean and standard deviation. The physicaltests showed high effectiveness (100%) in solubility, heating, and hexagonal tests, while turbidity–foamtest values varied: 90±0.22% (fresh honey), 80±0.41% (packaged honey), and 85±0.36% (comb honey).Chemical analyses revealed that HMF (0 mg/kg) and diastase activity (5.18–5.52 DN) met SNI 8664:2024standards. However, moisture content in packaged (23.8±0.29%) and comb honey (22.2±0.25%), aswell as water insoluble solids (0.51%–0.64%), slightly exceeded the SNI limits. Overall, both comb andpackaged honey from Bojongmurni Beekeeping Area were confirmed to be pure honey.